Farmers Perception on Application of Technology and Economics Innovation of Spice Coffee - Indra Tjahaja Amir; Pawana Nur Indah; Sri Widayanti (Nusantara Science and Technology Proceedings)
The role of agroindustry in rural areas in increasing the added value of agricultural commodities especially in the creation of value added, employment absorption, and linkage with other sectors. Most of the coffee is cultivated by smallholder plantations. The quality of coffee is low because most farmers pick it in the same way and process it dry. People traditionally know the spices coffee give priority to certain flavor and aroma. The objective of the research is a) to analyze the application level of technological innovation of spice coffee farmers and b) to analyze the application level of economic innovation of coffee farmers. The analysis used is description about perception of applying innovation of the spice coffee industry. The results showed that the main perception of coffee farmers to implement technological innovation is the spice coffee technology does not cause damage to the local environment, even using local raw materials, such as ginger, kencur, keningar, cardamom and cumin. Another perception is packaging technology and processing of spice coffee that is easy to apply. The main perception of coffee farmers to implement economical innovation is to increase profits and selling points. In addition, it is easy to market, close input market location and taste of spice coffee aromatic.